Severe drug eruption after antibiotic administration in patients receiving immune checkpoint inhibitors: A monocentric case series - Aya Nishizawa; Koichi Takeda; Tetsuya Urasaki; Makiko Ono; Toshiaki Mochizuki; Taro Shiga; Motohiro Fujiwara; Takeshi Yuasa; Atsushi Murakami; Ryo Koike; Mayu Yunokawa; Hiroyuki Kanao; et al. (Wiley, 2023)
Abstract Immune checkpoint inhibitor (ICI) therapy is often associated with cutaneous immune‐related adverse events (irAEs). Drug eruptions stemming from concomitantly or consecutively administered medications are also frequent and tend to be severe. We herein present three cases of severe drug eruption in patients receiving antibiotics during ICI therapy in which hypotensive shock occurring during antibiotic administration was followed by generalized erythema and prolonged organ damage. Three patients received tazobactam/piperacillin (TAZ/PIPC) for an infection during ICI treatment. A high fever developed in all the patients after a switch was made to other antibiotics (Figures 2-4). Since no skin rash was observed at fever onset, a flare‐up of the infection was suspected, and TAZ/PIPC administration was resumed. Thereafter, the patients suddenly experienced hypotensive shock and respiratory failure requiring ICU management for generalized erythema and organ damage. Since anaphylaxis caused by TAZ/PIPC is rare, the patients' clinical findings might be a manifestation of synergistic, complementary, immunomodulatory effects of ICI. In patients receiving ICI therapy, a fever occurring during antibiotic administration may indicate the onset of an immune hypersensitivity reaction to the drug. Resumption of antibiotic administration, especially TAZ/PIPC, during such a period may trigger an excessive inflammatory response, leading to an anaphylaxis‐like reaction and organ damage.